Molecular characterization and antibacterial immunity functional analysis of the antimicrobial peptide hepcidin from Coregonus ussuriensis berg. Issue 122 (March 2022) - Liu, Enhui; Huang, Tianqing; Gu, Wei; Wang, Gaochao; Dong, Fulin; Ma, Haibing; Zhang, Lanlan; He, Xianchen; Yao, Zuochun; Jiao, Wenlong; Li, Chunyu; Wang, Bingqian; et al.
Abstract: Antimicrobial peptides are immune system molecules existing in different organisms including mollusks, crustaceans and vertebrates. Hepcidins are a group of cysteine rich antimicrobial peptides, which plays an important role in fish response to a variety of pathogens. In this study, we cloned and identified Hepcidin from the Coregonus ussuriensis Berg, and its functions in vivo and in vitro was investigated. Our results showed that, CuHepc contains a 267 bp coding sequence (CDS) region that encodes 88 putative amino acids with a molecular weight of 9.77 kD. Hepcidin transcripts were most abundant in the liver of healthy C. ussuriensis Berg. The synthesized Hepcidin peptide exhibited a wide range of antibacterial activity against Gram-positive and Gram-negative bacteria in vitro, and the results of in vivo bacterial attack assays showed that the CuHepc gene was differentially up-regulated in the six tissues investigated after infection with Aeromonas hydrophila . To analyze the changes in protein levels in C. ussuriensis, we generated Hepc polyclonal antibodies in rabbits and verified that the protein expression was increased after bacterial infection with Western blot assay. MIC assay results showed a geometric mean value of 5.513 μM for CuHepc peptide. In the in vivo experiment, immune-related genes IL-10, NF-κB, TLR3 were up-regulated post-infection CuHepc peptide in liver and intestine. Finally, CuHepc peptide reduced the tissues microbial load compared to infection with Aeromonas hydrophila . The above results indicate that Hepc plays a role in the immune response of C. ussuriensis to exogenous disturbances, indicate that CuHepc might act a candidate for modulation of the innate immune system in C. ussuriensis . Highlights: The Hepcidin from C . ussuriensis Berg was cloned and identified, and its functions in vivo and in vitro was investigated. The Hepcidin peptide exhibited a wide range of antibacterial activity against Gram-positive and Gram-negative bacteria. The antimicrobial effect of CuHepc on A.hydrophila may related to the reduction in tissues microbial load.